Perlindungan Data Pribadi Nasabah Tunanetra Dalam Mengakses Perbankan - Alfan Rizky Ardhanta; Riky Rustam (Fakultas Hukum Universitas Islam Indonesia, 2024)
Banking is a public service that can be accessed by all people, including the blind, but there are problems for the blind in accessing banking which causes the blind to be discriminated against. The problem formulation involves questions related to the problems of account ownership for blind customers and mechanisms for protecting the confidentiality of blind customer data in the banking sector. The research method used is a normative legal research method with a statutory regulatory approach and a conceptual approach. The research results show that there are problems for blind customers in accessing banking, namely limited accessibility, technical obstacles such as administrative problems due to not being able to sign, data security risks and inadequate legal protection due to the absence of an effective legal framework for the special needs of the blind. The legal protection mechanism for blind customers is by opening a joint account which is enhanced by being accompanied rather than represented in accessing banking, absorbing PTO into legislation, banking administration problems can imitate other countries such as Hong Kong, and using preventive and repressive protection. The suggestion in this research is to improve regulations that are effective, efficient and uniform to minimize the problems of blind customers in the banking sector by taking into account the special conditions of the blind. And the OJK together with Bank Indonesia need to review regulations to create a holistic legal basis for synchronization and improve digital education and literacy for blind customers, including the development of appropriate banking technology.